1994
DOI: 10.1111/j.1600-0447.1994.tb01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Criminality and platelet monoamine oxidase activity in former juvenile delinquents as adults

Abstract: Platelet monoamine oxidase (MAO) activity was estimated in 70 former delinquent boys and 40 controls now aged 38-46 years. Platelet MAO activity was compared with their early criminal behaviour (before the age of 15) and their late registered criminality from the age of 15). Mean platelet MAO activity in subjects with both early and late criminality was significantly lower than that in former delinquents without late criminality. There was no significant difference in mean platelet MAO activity between control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…In summary, it has been suggested that platelet MAO-B activity might add predictive validity and clinical accuracy in forensic psychiatric settings [68] . This study did not support such an assumption.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, it has been suggested that platelet MAO-B activity might add predictive validity and clinical accuracy in forensic psychiatric settings [68] . This study did not support such an assumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially hyperactive behavior in childhood/adolescence has been found to be one of the more influential prestages of adult psychosocial disturbances and in particular psychopathy (af Klinteberg, 1996(af Klinteberg, , 1997Lynam, 1998;Satterfield, 1987). Hyperactivity has furthermore been found to be associated with certain dysfunctioning psychobiological underlying mechanisms (af Klinteberg & Oreland, 1995;Shaywitz, Shaywitz, Cohen, & Young, 1984), interestingly also found in groups of psychopathic criminals (Alm et al, 1994;Garpenstrand et al, 2002;Lidberg, Modin, Oreland, Tuck, & Gillner, 1985).…”
Section: Hyperactivity In Childhood and Pursuant Psychopathic Traits mentioning
confidence: 93%
“…A marked negative relationship exists between CSF 5-HIAA and MOA-activity on the one hand and the degree of sensation-seeking and psychopathic impulsivity on the other (Alm et al 1994;Dolan 1994). There is an association between low serotonin (5-hydroxytryptamine, 5-HT) function and aggressive behavior (Dolan 1994).…”
Section: Neurobiological Psychological and Social Variablesmentioning
confidence: 99%